Performance and age of African and non-African runners in World Marathon Majors races 2000-2014 - Knechtle, B.; Aschmann, A.; Onywera, V.; Nikolaidis, P. T.; Rosemann, T.; Rüst, C. A. (Journal of Sports Sciences, 2017)
The age for the fastest marathoners is well investigated, but not the age and nationality of the fastest. We investigated the age of peak marathon performance for the annual top 100 women and men competing in four races of the "World Marathon Majors" (Boston, Berlin, Chicago and New York) and the "Stockholm Marathon" between 2000 and 2014 using mixed-effects regression analyses and one-way ANOVA. Race times of Ethiopian men decreased to 2:14 h:min, but remained unchanged for Kenyan (2:14 h:min), Moroccan (2:15 h:min) and South African (2:18 h:min) men. Race times in Ethiopian (2:34 h:min), Kenyan (2:29 h:min) and South African (2:49 h:min) women showed no changes. Age increased in Ethiopian and South African men to 29.0 ± 5.0 and 32.0 ± 1.0 years, respectively. Age for Kenyan (29.9 ± 2.0 years) and Moroccan (34.9 ± 3.9 years) men remained unchanged. Age remained unchanged for Ethiopian (26.5 ± 2.0 years), Kenyan (30.0 ± 0.8 years) and South African (36.3 ± 7.0 years) women. In summary, Ethiopian men improved marathon race times, but not Ethiopian women. Age increased in Ethiopian men, but not in Ethiopian women. For practical applications, female and male marathoners from Ethiopia were the youngest and the fastest.